Efektifitas Konseling Kesehatan Reproduksi Terhadap Peningkatan Pengetahuan Kesehatan Reproduksi Pasangan Calon Pengantin di KUA Kota Padang - Harly Pratiwi Indah; Desmiwarti Desmiwarti (Andalas Obstetrics And Gynecology Journal, 2019)
Objective : To find out the effectiveness of reproductive health counseling on reproductive health knowledge for bride and groom couples in the KUA, Padang City, October 2017 - March 2018.Methods : This study is an analytical study using a cross-sectional study design with a population, namely couples who received prenuptial counseling and a sample of respondents who received prenuptial counseling at KUA Padang City during the period October 2017 - March 2018. The sample was taken using simple random sampling technique. The data were taken from post counseling questionnaires that were distributed to the prospective bride and groom couples. Data were analyzed by univariate and bivariate using chi-square test and independent T test with 95% CI. The research results are presented in tabular form.Results : During the study period, 147 respondents were given a post-counseling questionnaire on reproductive knowledge. It is known that more than half of the respondents (61.2%) had a low level of education, namely elementary, junior high and high school education, while 38.8% of respondents had higher education, namely at the diploma, undergraduate and postgraduate levels. Of the 147 respondents, more than half (79.6%) with a high level of knowledge about reproductive health after being given prenuptial counseling and all respondents (100%) stated that premarital counseling was beneficial. And it can be concluded that there is no difference in the mean age between respondents with high knowledge of reproductive health after being given counseling with low knowledge (p> 0.05). The results of the analysis showed that there was a significant relationship between the education level of the respondents and knowledge about reproductive health after being given counseling (p <0.05).Conclusion : More than half of the respondents (79.6%) have a high level of knowledge about reproductive health after being given pre-marital counseling on reproductive health.Keywords: Pre-marital Counseling, Reproductive Health